Aruncus dioicus var. kamtschaticus extract suppresses mitochondrial apoptosis induced‐neurodegeneration in trimethyltin‐injected ICR mice. Issue 6 (14th September 2018) - Park, Su Bin; Kang, Jin Yong; Kim, Jong Min; Park, Seon Kyeong; Park, Sang Hyun; Kang, Jeong Eun; Lee, Chang Jun; Kwon, Bong Seok; Yoo, Seul Ki; Lee, Uk; Kim, Dae‐Ok; Heo, Ho Jin
Abstract: In the present study, we attempt to confirm the effect of the ethyl acetate fraction from Aruncus dioicus var. kamtschaticus (EFAD) against neurodegeneration with various experiments using trimethyltin (TMT). First, learning and memory deterioration caused by TMT was examined with several behavioral tests. EFAD had an improvement effect on TMT‐induced cognitive dysfunction. Second, to assess the oxidative stress caused by TMT, a series of biochemical indicators of the cholinergic and antioxidant system were measured. EFAD showed superb effects on the recovery of the cholinergic system and reduction of oxidative stress. Third, to identify the mitochondrial apoptosis caused by TMT, mitochondrial activity and mitochondrial apoptotic signaling molecules were analyzed. EFAD improved mitochondrial activity and suppressed mitochondrial apoptosis. Finally, dicaffeoylglucose isomers were identified as main compounds of EFAD with ultra‐performance liquid‐quadrupole‐time‐of flight mass spectrometry (UPLC‐QTOF/MS 2 ). Consequently, EFAD showed a protective effect against mitochondrial apoptosis‐induced neurodegeneration in TMT‐injected mice based on antioxidant ability. Practical applications: Recently, neurodegenerative disease patients are increasing, and in particular, Alzheimer's disease (AD) is a representative neurodegeneration, which characterized by mitochondrial damage, neurofibrillary tangles, and neuronal cell death. This study confirmed that the ethyl acetate fraction from A. dioicus var. kamtschaticus ameliorates the impaired cognitive ability by TMT toxicity, which shares the symptoms of AD. Therefore, this study can provide the potential of cognitive functional food material of A. dioicus var. kamtschaticus.